Taxonomic review of the subfamily Bradyporinae (Orthoptera: Tettigoniidae; Bradyporini; Ephippigerini) of Turkey, with description of new species and the relationship of the taxa - Ünal, Mustafa (Zootaxa, 2011)
The members of the subfamily Bradyporinae including Bradyporini and Ephippigerini found in Turkey are studied. Two phylogenetic relationships based on morphology for the subgenera, species groups and for the all species of Bradyporus s.l. are proposed. A new diagram shows together the relationships and the schematized distributions of the taxa, Geographical Network Relationship, is proposed. A synonymic checklist of the known species of Bradyporus s.l. is given. Taxonomical changes, the doubtful and uncertain taxa names are discussed. Callimenus Fischer von Waldheim, 1830 is proposed as a subgenus of Bradyporus Charpentier, 1825. Four species groups, B. oniscus sp. group, B. macrogaster sp. group, B. dilatatus sp. group and B. latipes sp. group, are separated. Callimenus macrogaster pancici Brunner, 1882 is synonymized with Bradyporus (Callimenus) macrogaster longicollis (Fieber, 1853). Neotypes for B. (s.str.) dasypus (Illiger, 1800) and B. (Callimenus) macrogaster macrogaster (Lefebvre, 1831) are designated. Five new species, Bradyporus (Callimenus) avanos sp. n., B. (Callimenus) sureyai sp. n., B. (Callimenus) conophallus sp. n., B. (Callimenus) toros sp. n. and B. (Callimenus) karabagi sp. n. are described. Bradyporus (Callimenus) latipes (Stål, 1875) is recorded from Turkey for the first time. The species Schulmeisteri schulmeisteri Harz, 1992 is excluded from the subfamily Bradyporinae. All previous records of Bradyporinae species in Turkey with full synonymic list of each species are given. The previous misidentifications are determined and then the distribution of each species is adjusted. The characters used the separation of the taxa are briefly discussed. The titillator for Turkish species and the basal projecting of ventral valve of ovipositor are used for the first time. Descriptions and redescriptions of the studied Bradyporus species are given. Keys to tribes, subgenera, species groups and Turkish species of Bradyporus are provided. In addition 157 original figures including a distributional map are provided.